Crucial Optimization of Translational Components towards Efficient Incorporation of Unnatural Amino Acids into Proteins in Mammalian Cells - Xiang, Liang; Moncivais, Kathryn; Jiang, Faqin; Willams, Blake; Alfonta, Lital; Zhang, Zhiwen J. (PLOS ONE, 2013)
The ability to site-specifically incorporate unnatural amino acids (UAAs) into proteins is a powerful tool in protein engineering. While dozens of UAAs have been successfully introduced into proteins expressed by Escherichia coli cells, it has been much more challenging to create tRNA and tRNA-Synthetase pairs that enable UAAs incorporation, for use in mammalian systems. By altering the orthogonality properties of existing unnatural pairs, previously evolved pairs for use in E. coli could be used in mammalian cells. This would bypass the cumbersome step of having to evolve mutant synthetases and would allow for the rapid development of new mammalian pairs. A major limitation to the amount of UAA-containing proteins that can be expressed in the cell is the availability of UAA-charged orthogonal suppressor tRNA. By using a natural mammalian tRNA promoter, the amount of functional suppressor tRNA can be greatly increased. Furthermore, increasing recognition of the suppressor tRNA by the mutant synthetase will ultimately lead to the appearance of more UAA-charged tRNA.